Entropy demystified : the second law reduced to plain common sense - Ben-Naim, Arieh, 1934- (World Scientific, 2008)
In this unique book, the reader is invited to experience the joy of appreciating something which has eluded understanding for many years - entropy and the Second Law of Thermodynamics. The book has a two-pronged message: first, that the second law is not infinitely incomprehensible as commonly stated in most textbooks on thermodynamics, but can, in fact, be comprehended through sheer common sense; and second, that entropy is not a mysterious quantity that has resisted understanding but a simple, familiar and easily comprehensible concept. Written in an accessible style, the book guides the read.